2014
DOI: 10.1136/tobaccocontrol-2014-051635
|View full text |Cite
|
Sign up to set email alerts
|

Fine particulate matter concentrations in smoking households: just how much secondhand smoke do you breathe in if you live with a smoker who smokes indoors?

Abstract: Fine particulate pollution in Scottish homes where smoking is permitted is approximately 10 times higher than in non-smoking homes. Taken over a lifetime many non-smokers living with a smoker inhale a similar mass of PM2.5 as a non-smoker living in a heavily polluted city such as Beijing. Most non-smokers living in smoking households would experience reductions of over 70% in their daily inhaled PM2.5 intake if their home became smoke-free. The reduction is likely to be greatest for the very young and for olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 21 publications
3
42
0
1
Order By: Relevance
“…This is particularly relevant if we consider that there are more common sources of pollution that are not accounted for. For example, living with a smoker exposes an individual to levels of toxicants that are comparable with those of a heavily polluted city [Semple et al 2014].…”
Section: Air Quality and Respiratory Allergiesmentioning
confidence: 99%
“…This is particularly relevant if we consider that there are more common sources of pollution that are not accounted for. For example, living with a smoker exposes an individual to levels of toxicants that are comparable with those of a heavily polluted city [Semple et al 2014].…”
Section: Air Quality and Respiratory Allergiesmentioning
confidence: 99%
“…Semple et al [49] said that median PM 2.5 concentrations from 93 smoking homes were 31 μg/m 3 (ranged between 10 and 111 μg/m 3 ) and 3 μg/m 3 (ranged between 2 and 6.5) μg/m 3 for the 17 non-smoking homes and still showed that non-smokers living with smokers typically have average PM 2.5 exposure levels more than three times higher than the WHO guidance for annual exposure to PM 2.5 (10 μg/m 3 ). So, PM 2.5 pollution in indoor ambient where smokers live is approximately 10 times higher than that of non-smoking.…”
Section: Evaluation Of Indoor Air Pollution and Comparison With The Umentioning
confidence: 99%
“…SHS can sensitise children to nicotine, possibly increasing risk of smoking in adolescence 15 16. Children’s greatest risk of SHS exposure is in the home 17–19…”
Section: Introductionmentioning
confidence: 99%